Dextrocardia with Situs Inversus Totalis - A Rare Anatomical Variation: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
A 35-year-old female dead body was brought to the mortuary for post-mortem examination as a burn case. During examination, incidentally, we found that there was an anatomical variation termed as situs inversus totalis. The term situs inversus is a short form of the Latin phrase ‘situs inversus viscerum’, meaning inverted position of the internal organs. The situs inversus totalis is a rare syndrome, with an estimated prevalence of 1 in 10,000 births, characterised by the inverted position of the thoracic and abdominal organs with respect to the sagittal plane. Situs inversus totalis, a not so uncommon congenital positional anomaly, can be a diagnostic problem at times. The condition affects all major structures within the thorax and the abdomen. Surgeons and radiologists need to be aware of this anomaly during preoperative and surgical management. Routine premedical examination helps the patient to be aware of his/her condition, thereby preventing wrong diagnosis and possibly death due to delay in surgical management; it can also be used as an identification parameter.
Keywords: Situs inversus totalis; Anatomical; Sagittal plane; Syndrome; Abdominal organ